2006
DOI: 10.1038/nsmb1125
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-dependent degradation of Est1p regulates the cell cycle–restricted assembly of telomerase in Saccharomyces cerevisiae

Abstract: Telomerase counteracts loss of terminal sequences incurred during DNA replication. In S. cerevisiae, telomerase contains an RNA template (TLC1), a reverse transcriptase (Est2p) and at least two regulatory proteins (Est1p and Est3p). Whereas Est2p is constitutively telomere bound, Est1p associates in late S phase, coincident with telomere lengthening. Here we directly demonstrate by coimmunoprecipitation that the composition of telomerase varies during the cell cycle. The absence of Est1p and Est3p from the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
137
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(154 citation statements)
references
References 45 publications
13
137
2
1
Order By: Relevance
“…In agreement with the effects on TLC1 association, Est3p ETN -HA 3 and Est3p DQ -HA 3 were reduced in their ability to co-immunoprecipitate with Myc 18 -Est2p (Fig. 2B) [13][14][15][16][17][18] in the identical immunoprecipitation. Results are representative of two independent biological replicates (see supplemental Fig.…”
Section: Est3 Mutant Alleles Alter Telomerase Assembly and Function Isupporting
confidence: 64%
See 3 more Smart Citations
“…In agreement with the effects on TLC1 association, Est3p ETN -HA 3 and Est3p DQ -HA 3 were reduced in their ability to co-immunoprecipitate with Myc 18 -Est2p (Fig. 2B) [13][14][15][16][17][18] in the identical immunoprecipitation. Results are representative of two independent biological replicates (see supplemental Fig.…”
Section: Est3 Mutant Alleles Alter Telomerase Assembly and Function Isupporting
confidence: 64%
“…Telomerase-We showed previously that Est1p stimulates the assembly of Est3p with telomerase (15). However, our failure to detect an Est1p/Est3p interaction by coimmunoprecipitation from cell extract in the absence of Est2p suggested that Est1p might not be the primary binding site for Est3p (15).…”
Section: A Direct Est2p/est3p Interaction Contributes To the Assemblycontrasting
confidence: 48%
See 2 more Smart Citations
“…Intriguingly, mutations in CDC13 and EST1 that abolished telomere maintenance in vivo did not have an obvious effect on this physical interaction, suggesting that a step other than recruitment may be affected. Besides interacting with Cdc13, Est1 has also been implicated in promoting the assembly of Est3 into the telomerase complex (44,45). Using a similar approach, Zakian and colleagues also demonstrated a direct and specific physical interaction between Est1 and Est3, thus providing a plausible mechanism for how this assembly function is achieved (46).…”
Section: Regulation By Telomere Proteins and Accessory Factorsmentioning
confidence: 90%